On Publication Strategies. Another Advice to a Beginning Scientist - Coronel, Ruben (Frontiers in Physiology, 2020)
Productivity in science has increased and it is becoming more important for a scientist to publish, to publish frequently and to accumulate citations to their work. However, the peer review system may not only promote and advance but also hinder, prevent or delay publication. Confirmatory, consensual, competitive and controversial publication strategies are here described that may meet with various degrees of approval or disapproval from the author’s peers. The selected publication strategy may impact on the development of a career. Resolving controversies helps science advance efficiently. Therefore, controversies should be sought and addressed, although preferably not at the start of a career. No abstract